A ground book on engineering mathematics - Mukherjee, Arup Kumar (Shreedhar Prakashani, 2019)
A ground book on engineering mathematics / Mukherjee, Arup Kumar. -- Kolkata: Shreedhar Prakashani, 2019 510 M941e2V1AV1B 2nd ed No. of Copies : 2